Design and Development of Augmented Reality based Virtual Pet Simulator Game to simulate Pets Behaviors - Ng, Jun Wen; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2021)
Augmented reality is an enhanced version of the real physical world integrated with 3D representation that helps users to understand an abstract concept. This paper discussed the design and development of ‘smARt CAT’, an AR virtual pet game. smARt CAT is a virtual application that uses Augmented Reality (AR) technology to display a virtual pet, to enhance the users’ experience. Through the smARt CAT application, users can also understand the daily behaviors of pets while self-curing loneliness or depression. The application development methods are carried out starting from idea creation, design, development, testing and release phases based on Mobile Software Development Lifecycle (Mobile SDLC). This application is developed by using the Unity3d game engine and combine with the AR technique which is ARCore. Furthermore, the artificial intelligent part which is voice recognition is added to the application. Testing results from 20 respondents which are children between 6 to 12 years old shows that the application was received more positive feedback. About 80% of the respondents enjoy playing smARt CAT, therefore showing the acceptance rate of the application.